Procedimientos de Ordeño: Pasos para Mejorar la Calidad de la Leche y Eficiencia al Ordeñar las Vacas - Izabella Toledo (EDIS)
This brochure shows steps to improve milk quality and efficiency when milking cows. Written by Izabella Toledo, and published by the UF/IFAS Department of Animal Sciences, October 2021.